1995
DOI: 10.1121/1.412817
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and pitch strength of iterated rippled noise

Abstract: A cascade of add, delay (d ms), and attenuate (−1≤g≤1) circuit excited with noise produces iterated rippled noise (IRN) stimuli. The matched pitch and discriminability between pairs of IRN stimuli were studied as a function of g, d, and the number of circuit iterations (n). For g≳0, the pitch of all IRN stimuli equals 1/d. For g<0, pitch depends on n: For small n, there were two pitches in the region of 1/d, while for large n there was a single pitch equal to 1/2d. Peaks in the autocorrelation function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 0 publications
6
63
2
3
Order By: Relevance
“…The similarities in pitch strength judgments for noise-vocoded wHTCs and IIRNs establish the saliencies evoked by noise-vocoded wHTCs as meaningful in terms of pitch percepts. Previous studies on pitch strength using magnitude judgment have concluded that saliency is related to temporal properties of the stimuli (Yost, 1996b;Shofner and Selas, 2002). However, in the present study, the predicted judgments based on temporal structure (i.e., PS or AC1) do not account for the actual judgments of listeners' pitch strength [Figs.…”
Section: Discussioncontrasting
confidence: 53%
“…The similarities in pitch strength judgments for noise-vocoded wHTCs and IIRNs establish the saliencies evoked by noise-vocoded wHTCs as meaningful in terms of pitch percepts. Previous studies on pitch strength using magnitude judgment have concluded that saliency is related to temporal properties of the stimuli (Yost, 1996b;Shofner and Selas, 2002). However, in the present study, the predicted judgments based on temporal structure (i.e., PS or AC1) do not account for the actual judgments of listeners' pitch strength [Figs.…”
Section: Discussioncontrasting
confidence: 53%
“…It has been argued that pitch strength is directly related to the height of AC1 in the stimulus autocorrelation function Yost, 1996b;Yost, Patterson, & Sheft, 1996). With the use of a scaling procedure to measure the pitch strengths of iterated rippled noises, Yost (1996b) described the relationship between AC1 and pitch strength with the exponential function described by Equation 2.…”
Section: Discussionmentioning
confidence: 99%
“…If the second stimulus had a pitch strength between that of the first and third stimuli, the pitch strength of the second stimulus should be assigned a rating that is scaled relative to the pitch strengths of the first and third stimuli. This procedure is identical to that used by Yost (1996b). If needed, the listeners could listen to any trial repeatedly until they felt confident enough to assign a rating to the perceived pitch strength.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations